2022
DOI: 10.1111/coep.12562
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 lockdown and traffic accidents: Lessons from the pandemic

Abstract: We use a regression discontinuity design to study the effect of the COVID-19 lockdown on traffic accidents. Based on administrative data from Louisiana, we find that the lockdown order led to a significant decrease in traffic accidents (−47%), including accidents involving injury (−46%) and ambulance (−41%). We also find evidence of heterogeneous changes in the decline of drivers involved in accidents, with a smaller decline among individuals aged 25 to 64, male, and nonwhite drivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Qatar observed 73% drop in traffic violations and 37% drop in traffic accidents during the period of COVID-19-related preventive measures ( 14 ). Somewhat similar percentage reductions were reported for Louisiana, U.S., by Barnes et al who found 46% reduction in traffic accidents involving injuries ( 5 ). Katrakazas et al explored driving behavior in Greece and the Kingdom of Saudi Arabia (KSA) using data collected through mobile phone applications ( 25 ).…”
Section: Literature Reviewsupporting
confidence: 79%
See 1 more Smart Citation
“…Qatar observed 73% drop in traffic violations and 37% drop in traffic accidents during the period of COVID-19-related preventive measures ( 14 ). Somewhat similar percentage reductions were reported for Louisiana, U.S., by Barnes et al who found 46% reduction in traffic accidents involving injuries ( 5 ). Katrakazas et al explored driving behavior in Greece and the Kingdom of Saudi Arabia (KSA) using data collected through mobile phone applications ( 25 ).…”
Section: Literature Reviewsupporting
confidence: 79%
“…Consequently, various countries of the world saw unparalleled changes in mobility pertaining to different sectors ( 3 , 4 ). The substantial reduction in mobility also affected the accident and fatality rates ( 5 ). It can be noted that the non-pharmaceutical intervention (NPI) policies varied widely across different countries, ranging from restrictions on international and domestic travel to the curtailment of public and private gatherings ( 2 ).…”
mentioning
confidence: 99%
“…The trajectory of the more urgent ED care visits contrasts that of the less‐urgent preventive care visits, which supports our Hypothesis 2, suggesting that the reduced ED visits could reflect the reduced transmission of other infectious diseases because of improved health‐protective behaviors (Chiu et al., 2020), and reduced air pollution (Chen et al., 2020; He et al., 2020). The incidence of injuries could have been lowered because of reduced work and traffic accidents during the pandemic (Barnes et al., 2022; Qi et al., 2022). Additionally, the 10%–18% reductions in ED and chronic care visits by October 2020 observed in our sample could include some unnecessary or inappropriate care that was spared for the benefit of patients and the healthcare system (Moynihan et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, conclusions based on excess mortality potentially confound true deaths with other changes as a result of the pandemic. For example, Barnes et al (2020) and Oguzoglu (2020) report a reduction in traffic accidents and fatalities across Louisiana and 31 metropolitan areas in Turkey, respectively, due to implementation of various social distancing measures. Dang and Trinh (2020) documents a significant reduction of air pollution in Vietnam due to the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%